Risk-Assessment of Esophageal Surgery: Diagnosis and Treatment of Celiac Trunk Stenosis - Lammerts, Rosa G.M.; van Det, Marc J.; Geelkerken, Rob H.; Kouwenhoven, Ewout A. (The Thoracic and Cardiovascular Surgeon Reports, 2018)
Anastomotic leakage of the gastric conduit following surgical treatment of esophageal cancer is a life-threatening complication. An important risk factor associated with anastomotic leakage is calcification of the supplying arteries of the gastric conduit. The patency of calcified splanchnic arteries cannot be assessed on routine computed tomography (CT) scans for esophageal cancer and, as such, in selected patients with known or assumed mesenteric artery disease, additional CT angiography of the abdominal arteries with 1 mm slices is strongly encouraged. If the mesenteric perfusion is compromised in patients with resectable esophageal cancer, angioplasty procedures with stenting of the mesenteric arteries could be performed to prevent possible ischemia of the gastric conduit.
Keywords: atherosclerosis; endovascular procedures/stents; except PCI; imaging (all modalities); perfusion; stents; esophagectomy; complications